PENINGKATAN KEMAMPUAN MENULIS DESKRIPSI DENGAN METODE OBSERVASI TERPADU SISWA KELAS X SMK PGRI PAKISAJI MALANG - Ina Roudhotul Jannah (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2018)
Writing is a skill that language is used to communicate indirectly and not face-to-face with other people. Writing skills do not come naturally, but it requires adequate exercises. This study examines the learners’ problems in essay writing descriptions using the integrated observation learning methods. The lack of ability of the students in writing a description is due to lack of interest of students to learn, teachers’ traditional methods in teaching, and the theory – oriented activities without practice writing especially writing descriptions. The use of an integrated observation method proved to increase the ability of students to write descriptions. It can be taken from the test given to the students to write descriptions. With integrated observation learning, learners are able to generate ideas into writing descriptions by conducting an observation during the learning takes place. An observation was done outside of the classroom and school environment as well as just around the backyard of the school, so the students have a lot of good ideas to compose a good essay. Key Words: Improved, writing, descriptions, integrated observation method.